The Traditionalism of the Islamic Boarding School Education System in the Era of Modernization - Arifin, M. Zainal (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
In a system, education cannot be separated from the various life systems that surround it. The education system must always metamorphose towards a more ideal level. In the modern era, it is assumed that traditional Islamic boarding schools will experience changes, but the problem is when carrying out changes (modernization) do salafiyyah Islamic boarding schools leave their traditions? This study aims to find out how the policy of the Islamic boarding school will be carried out when there is a need to maintain its traditions and the desire for modernization? This is because the connotations between tradition and modernization are two camps that are difficult to unite. Answering these questions, the Assya`roniyyah Islamic Boarding School is used as a material for discussion, using qualitative descriptive methods and historical sociological and phenomenological approaches the author tries to analyze the education system that is run. The results of the research show that the education system of the Assya`roniyyah Islamic Boarding School is a combination of elements of traditionalism and modernization. The renewal of the salafiyyah Islamic boarding school education system on the one hand is a linear process, meaning that the elements of the education system have been updated in response to modernity, but on the other hand, there is a necessity to stick to the traditional paradigm. So, in essence, the changes that occur in the boarding school system are a process of changing the creation of integral education.